Aerial insectivorous bats in the Brazilian-Uruguayan savanna: Modelling the occupancy through acoustic detection - da Costa, Cíntia Fernanda; Ramos Pereira, Maria João (Frontiers in Ecology and Evolution, 2022)
The Pampa is the least protected and one of the least sampled for bats among the Brazilian domains. This leads to significant Linnean and Wallacean shortfalls for bats in the Brazilian-Uruguayan savanna ecoregion. Here, our aim was to model the occupancy of aerial insectivorous bats in response to landscape structure at different scales, considering the influence of microclimate on bat detection. We acoustically monitored 68 locations during the spring and summer of 2019/2020, gathering data on temperature and humidity associated with each acoustic record using dataloggers. We detected at least 11 species of the Molossidae and the Vespertilionidae. The response to landscape structure was species-specific: the occupancy probability of Eptesicus brasiliensis and Molossus cf. currentium increased with landscape connectivity at the 500 m scale while Eptesicus furinalis and Histiotus cf. velatus were negatively affected by landscape connectivity at the 5.0 km scale. Molossus molossus occupancy probability responded negatively to landscape heterogeneity at the 3.0 km scale, while Promops centralis responded positively to landscape heterogeneity at the 5.0 km scale. Molossus rufus responded negatively to native vegetation cover and positively to landscape heterogeneity at the 5.0 km scale. Myotis albescens and Molossops temminckii did not respond significantly to any of the evaluated landscape metrics. Our results show that different bat species perceive the landscape differently, regardless of the guild of use of space – edge- or open-space forager. Our estimate of projected occupancy for the areas contiguous to those sampled ranged from 0.45 to 0.70 for the whole of the bat taxa, suggesting that the landscape, particularly where it still maintains its native elements, is reasonably favourable to aerial insectivores.